2002
DOI: 10.1256/003590002320603557
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of regional climatic effects of vegetation change in China

Abstract: SUMMARYIn the context of a regional climate model (RegCM2), simulation is undertaken of climatic effects of changed vegetation over China with their possible mechanisms studied, reaching results which show that the increase in ood events over the Yangtze-Huai River valleys and the aggravation of north-China droughts are likely to be under the joint action of deserti cation of the northern grassland, and southern degradation of evergreen broadleaf trees, the latter seeming to be the primary factor. Severe veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 30 publications
2
17
0
Order By: Relevance
“…Their results show that the vegetation conversion from forest to farmland reduces summer precipitation in northern and western China and enhance precipitation in Southeast China. Similar results were deduced by Zheng et al (2002) by prescribing simultaneous vegetation degradation in the northern Chinese prairies and the southern evergreen forests. Furthermore, precipitation increases at the Indian East coast.…”
Section: Comparison To Other Model Studiessupporting
confidence: 81%
See 1 more Smart Citation
“…Their results show that the vegetation conversion from forest to farmland reduces summer precipitation in northern and western China and enhance precipitation in Southeast China. Similar results were deduced by Zheng et al (2002) by prescribing simultaneous vegetation degradation in the northern Chinese prairies and the southern evergreen forests. Furthermore, precipitation increases at the Indian East coast.…”
Section: Comparison To Other Model Studiessupporting
confidence: 81%
“…The impact of these land cover change has been analysed in several climate model studies (e.g. Zheng et al, 2002;Fu, 2003;Gao et al, 2007;Zhang and Gao, 2008). They all agree that the vast degradation of the land cover has caused a regional climate change.…”
mentioning
confidence: 99%
“…A number of recent studies have shown that the arid and semiarid areas in northern China have diminished during the last 20 years due largely to land management and afforestation (e.g., Piao et al 2005;Xue et al 2005), which, however, is in contrast to the strengthened anthropogenic activities (such as enhanced grazing and increased population) during the same period (Wang et al 2006b). Furthermore, since the rehabilitated areas are small compared to the existing areas of semiarid regions and sandy lands, it deems to be dubious whether the local to regional changes in the atmospheric circulation and rainfall distribution due to the vegetation restoration could be favorable for the maintenance of the rehabilitated areas (Zheng et al 2002;Sen et al 2004). Sen et al (2004) demonstrated in an idealized numerical simulation that even relatively large re-greening in northern China might be vulnerable without abundant water resources or intensive irrigation because vegetation reclamation would produce more intense precipitation rather than more frequent rainfall that is more appropriate to maintaining the rehabilitated areas.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Desertification and deforestation are two types of land-surface degradations that have been a major research focus of the scientific community over the last two decades or so because the land areas subject to desertification and deforestation expanded rapidly during the last century (e.g., Charney et al 1975;Dickinson and Henderson-Sellers 1988;Lean and Warrilow 1989;Shukla et al 1990;Nobre et al 1991;Henderson-Sellers et al 1993;Lean and Rowntree 1993;McGuffie et al 1995;Xue 1996;Hahmann and Dickinson 1997;Kanae et al 2001;Zeng et al 2002;Sen et al 2004).…”
Section: Introductionmentioning
confidence: 99%